Profile of Anemia and the Relationship between Hemoglobin Levels and Quality of Life in End-Stage Chronic Kidney Disease Patients undergoing Chronic Hemodialysis at Hasan Sadikin Hospital 2021-2022 - Hasibuan, Siti Fatimah; Makmum, Afiatin; Sukesi, Lilik (Indonesian Journal of Kidney and Hypertension, 2024)
Background: Anemia is a common complication of Chronic Kidney Disease (CKD). The severity of anemia has implications for patients' quality of life. Objective: This study aims to determine the profile of Anemia and the relationship between Hemoglobin (Hb) levels and the quality of life of end-stage CKD patients undergoing chronic Hemodialysis. Methods: This study is analytical observational research with a cross-sectional design approach to explore the correlation between Hb levels and the quality of life of routine Hemodialysis patients at Hasan Sadikin Hospital, Bandung, throughout 2021-2022. Hb levels were continuous data. The quality of life of CKD patients was measured using the Indonesian version of the KDQOL questionnaire based on eight components. The obtained data were statistically analyzed using Spearman's Rank correlation. Results: This study had 150 subjects, 75 male (50.0%) and an average age of 45. The most common etiology of CKD was hypertensive nephrosclerosis (52.7%). The average Hb level was 9 g/dL. The highest quality of life score was 68, and the lowest was 41.28, with a median of 50.99. The correlation analysis results showed an r of -0.157 and p of 0.057, indicating a very weak negative correlation that is not statistically significant. Conclusion: The study's conclusion indicates no relationship between Hb levels and the quality of life of end-stage CKD patients undergoing chronic Hemodialysis.